INTEGRASI SISTEM OPERASI DAN INFRASTRUKTUR AI DALAM MENINGKATKAN PERFORMA DAN KEANDALAN SISWI SMP IBRAHIMY 3 SUKOREJO - Zaehol Fatah; Nadia Selvi Ramadhani; Siti Imroatul Jannah (CV. Denasya Smart Publisher, 2025)
This seminar was held to introduce and unify ideas about Operating Systems and Artificial Intelligence (AI) among students of SMP Ibrahimy 3 Sukorejo. The main objective of this seminar is to instill a basic understanding in students about how AI and Operating Systems can work together to improve the quality of teaching and learning activities. This seminar is packaged with an interactive method and equipped with easy-to-practice explanations so that students can more easily understand and apply AI wisely. The results of this event show an increase in students' interest and practical insight into AI technology and awareness of its responsible application. By holding this seminar, it is hoped that students will have the initial capital to face the rapid progress of technology and be able to use it productively and ethically